Law's allure : how law shapes, constrains, saves, and kills politics - Silverstein, Gordon (Cambridge University Press, 2009)
Law's Allure explains how, when, and why America's reliance on legal rules and judicial decisions shapes, constrains, saves, and sometimes even kills politics.